Perceptions of sacrifice in the pursuit of sufficient consumption - Magnier, Lise; Kobus, Charlotte; Tunn, Vivian (Proceedings of the 6th Product Lifetimes and the Environment Conference (PLATE2025), 2025)
This study investigates the role of perceived sacrifice in the adoption of behaviours of sufficiency in clothing consumption. With the urgent need to reduce carbon emissions and consumption to stay within planetary boundaries, this research explores how consumers perceive and are willing to make sacrifices for sustainable consumption. The paper examines seven types of perceived sacrifices—functional, emotional, social, epistemic, conditional, financial, and time/effort—and their impact on the intention to adopt sufficiency behaviours such as reducing purchases, extending clothing longevity, shifting to second-hand items, and sharing clothes. The findings reveal that perceived sacrifices significantly and negatively influence the willingness to adopt these behaviours, with variations across different types of sacrifices and behaviours. This research contributes to the literature on sustainable consumer behaviour and offers insights for policy-makers, marketers and designers to promote sufficiency in consumption